Could Pradhan Mantri Garib Kalyan Yojana (PM-GKY) mitigate COVID-19 shocks in the agricultural sector: Evidence from Northern India - Varshney, Deepak; Kumar, Anjani; Mishra, Ashok K.; Rashid, Shahidur; Joshi, Pramod Kumar (International Food Policy Research Institute, 2020)
While the COVID-19 pandemic resulted about 24% decline in Indian GDP during April-June 2020 quarter, the nation’s agricultural sector, somewhat surprisingly, seems to have done remarkably well during the same period. Using phone survey of a sample of previously interviewed households from Northern India, this paper examines whether the package of public transfer program announced during the lockdown, called Pradhan Mantri Garib Kalyan Yojana (PM-GKY), has helped farmers deal with the shock. Overall, results show that 95 percent of the small holders received supports from at least one of the components of the PM-GKY scheme. Direct cash transfers have performed better than the in-kind transfer schemes. The econometric analysis, using a quasi-experimental method, suggests that the fungibility of funds received under the transfer package was significant in alleviating credit constraints and increasing agricultural investments in modern inputs. This is evident from the results that when only income support program (PM-KISAN) is considered, impact was limited to seed, not fertilizer and pesticides. By contrast, farmers who received benefits from all four programs (i.e., PM-KISAN, cash transfer for women, conditional cash transfers, and free food rations-KISAN) had spent significantly more on procurement of seeds, fertilizers, and pesticides.